'An American has been turned': Thinking Autoimmunity through Homeland. Issue 1 (May 2014) - Farred, Grant
<x xml:space="preserve">Abstract</x> This essay uses Derrida's concept of autoimmunity to critique Homeland, a television show that deals with an American prisoner of war who has been 'turned' into an operative for an al Queda-like movement. Autoimmunity is critical to thinking the ways in which the existence of a turned POW within the state, who belongs visibly to the state, presents a particularly heteronomic challenge to how the distinction between Self and Other operates. This Self who has taken up the cause of the Other presents, this essay argues, an infinitely greater threat to the state precisely because it cannot be identified as Other, precisely because bears no ostensible traces of the Other.